Photo‐Responsive and NGR‐Mediated Multifunctional Nanostructured Lipid Carrier for Tumor‐Specific Therapy. Issue 4 (28th January 2015) - Yang, Yanfang; Xie, Xiangyang; Yang, Yang; Zhang, Hui; Mei, Xingguo
<x xml:space="preserve">Abstract</x> A novel nanostructured lipid carrier (NLC) modified with photon‐sensitive cell penetrating peptides (psCPP) and Asn‐Gly‐Arg (NGR) was designed to enhance paclitaxel (PTX)‐targeted delivery and antitumor effect. The NGR moiety selectively binds to CD13‐positive tumors. On other hand, the psCPP moiety enhance specific cancer cellular uptake after rapidly cleaving the two‐photon excitation‐responsive protective group, in this case, illumination in the presence of near‐IR (NIR) light at the tumor site. The dual‐modified NLC (psCPP/NGR‐NLC) were prepared by emulsification method, and the concentrations of 1, 2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine‐polyethylene glycol 2000–psCPP (DSPE‐PEG2000‐psCPP) and DSPE‐PEG5000‐NGR in the NLC were chosen to be 4% and 1% (molar ratio), respectively. The mean particle size of the psCPP/NGR‐NLC was about 100 nm, and the drug entrapment efficiency was more than 90%. Stability study showed that the prepared NLCs were physically and chemically stable at 2°C–8°C up to 1 month. Cellular uptake results demonstrated that the proposed psCPP/NGR‐NLC had an enhancement of cancer cell recognition and specific uptake. Pharmacokinetic study showed that the prepared psCPP/NGR‐NLC possessed the long‐circulation characteristic with the t1/2 of 6.112 ± 0.304 h. Pharmacodynamics results confirmed that, with the aid of NIR illumination and NGR, the tumor inhibition ratio of psCPP/NGR‐NLC group was significantly higher than the other PTX groups. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:1328–1339, 2015